Guía teórica-práctica de ensamblaje de computadoras e instalación de software, aplicable al laboratorio de mantenimiento de la carrera de ingeniería en informática y sistemas computacionales de la Universidad Técnica de Cotopaxi - Caña Yacchirema, Fanny del Pilar (2014)
The present research about theoretical and practical guide on computer assembly and software installation, applicable for laboratory maintenance in systems engineering major at Technical University of Cotopaxi. One of the Aims is: To implement a guideline that enhances teaching practice with theoretical framework. The methodology is based on qualitative, quantitative, descriptive literature and field research. The last results have found the infrastructure is inadequate and it doesn’t have good learning environment for students when they want to practice, they need to practice computer assembly and the programs installation in their academic process, teachers and students say that “it is important to take decisions in order to solve problems”. Systems engineering is considered like a technical and practical career with constantly evolution, for that reason is necessary to improve technology in the educational institutions, so there is an urgent need: to implement maintenance laboratories and computing resources because they can improve the students’ skills when they want to improve their professionals competences, and finally the present work is an alternative proposal with an unique and original guide and it will benefit the university community.